Performance metrics of electrical conductors for aerospace cryogenic motors, generators, and transmission cables. (October 2020) - Sumption, M.D.; Murphy, J.; Susner, M.; Haugan, T.
Highlights: Metrics are developed for cryogenic normal state conductors for motors and generators. Cryogenic normal state conductors are compared to superconductors for use in motors and generators. Both cryogenic normal state conductors and superconductors strongly reduce the loss and total heat rejected. Mass reduction and better thermal management possible for systems with cryogenic fuel. Abstract: In this work we evaluate the performance of various electrical conductors, both normal-state and superconducting, at cryogenic temperatures with an eye towards motor, generator, and power transmission applications for use in all-electric and more-electric aircraft. In addition to MgB2 and YBCO superconductors, we consider high purity Cu and Al as well as carbon-nanotube (CNT) yarn. We analyze the normal-state conductors for current carrying capacity at room temperature as well as LN2 (77 K) and liquid hydrogen temperatures (20 K), where appropriate. To parameterize these materials for aerospace applications we have explored various options for defining current capacity metrics for these conductors at cryogenic temperatures. Paralleling definitions for ambient environment conductors, we first define electrical current capacity in terms of a limiting temperature rise for (i) windings directly immersed in a pool-boiling cryogen environment, and (ii) the case of thermal conduction though an epoxy winding. While neither metric is fully satisfactory, their implications are important. These results are then compared to a current capacity criterion developed in terms of a specified loss generation limit, which turns out to be a more meaningful approach. The results for these normal-state conductors operating at cryogenic temperatures are then compared to superconducting MgB2 and YBCO. After this, we consider two cases for overall system-level benefit in terms of power density, one for the case where the size of the cryogenic cooling apparatus is included, and a second case where the cooling is "free" (e.g., when liquid hydrogen is already onboard). We find total system weight reductions for the cryocooled case only for the superconducting options. If time varying magnetic fields are present, superconductor filament size must be kept small; an expression for limiting filament size is developed. For the case of "free" cooling, higher current levels are possible leading to reductions in winding size up to 16X using cryogenic normal-state conductors and values of 100–200X for superconducting options. The waste heat load is also substantially reduced because the total size of the winding is strongly reduced. This may significantly reduce the thermal management burden, a difficult problem for electric propulsion aircraft. We conclude that both superconductors and normal-state cryogenic conductors can increase power density in a case when liquid cryogen is "free", but only superconductors can lead to total system power density increases when heat cannot be rejected to the fuel.